The Impact of Oil-Related Income on the Equilibrium Real Exchange Rate in Syria - Dridi, Jemma (IMF Working Papers; Working Paper ;, 2008)
This paper examines the impact of oil-related income, among other fundamentals, on the equilibrium real effective exchange rate (ERER) in Syria. After reviewing the evolution of the Syrian multiple exchange rate regime since 1960 and assessing alternative measures for the exchange rate, the paper analyzes the impact of oil-related income on the ERER in the context of a behavioral equilibrium exchange rate model. The analysis concludes that ERER appreciates with higher oil-related income, productivity and net foreign assets, but, at odds with the conventional wisdom, depreciates with higher government expenditures given that an increase in expenditures usually translates into higher imports and weaker current account position. In light of the projected real shocks associated with the depletion of oil and the change in other fundamentals in the context of the ongoing transition to a market economy, a more flexible regime would serve Syria better in the future.